NEED FOR DEVELOPING HUMAN CAPITAL MANAGEMENT IN SMEs - Lucia Teresa Soberanes Rivas; Margarita Gonzalez Cano; Flor de Maria Mendoza Austria (European Scientific Journal, ESJ, 2013)
This research work is a documentary that exposes the importance of training and human capital development in SMEs, particularly the manager, for the decisions they make and carry the same significance in both the external and internal environment of the company. It mentions the need to investigate the effect of training and human capital development manager in the growth and survival of SMEs.